“Transnacionalidad” y actualización de la memoria de la violencia: el caso de El Salvador - Laura Fotia (Confluenze)
The scholarly debate on memory policies in Central America has evolved significantly, emphasizing their critical role in contemporary political agendas. This article, drawing on extensive primary and secondary sources, seeks to reconstruct and analyze the establishment and operations of El Salvador’s Espacio de Memorias y Derechos Humanos. It highlights the EMDH’s links to the nation’s transitional and restorative justice processes while exploring its contributions to emerging transnational memory practices.